Implementation and Performance of Lightweight Authentication Encryption ASCON on IoT Devices - Gabriela Cagua; Valerie Gauthier-Umana; Carlos Lozano-Garzon (IEEE Access)
The Internet of Things (IoT) is growing rapidly, enabling interconnected devices to communicate and share data seamlessly. While this expansion drives significant advancements across industries, it also introduces critical challenges in ensuring secure device communication. IoT devices often operate under strict constraints in processing power, memory, and energy consumption, complicating the implementation of robust security measures. Lightweight cryptographic algorithms have emerged to address these challenges, with ASCON gaining recognition for its robustness and efficiency. Selected as the winner of the National Institute of Standards and Technology (NIST) competition for lightweight encryption algorithms, ASCON ensures confidentiality and integrity through authenticated encryption with associated data (AEAD) tailored for resource-constrained environments. This paper presents the implementation and performance analysis of ASCON on IoT devices. Using the CupCarbon simulator framework, optimized for modeling smart cities and wireless sensor networks, we evaluate its effectiveness under resource-limited conditions. Performance metrics are analyzed, including latency, response times, and resource utilization. Additionally, ASCON is implemented on Raspberry Pi devices to validate its feasibility in real-world scenarios. Results demonstrate that ASCON enables efficient and secure communications while minimizing computational overhead, making it a viable solution for IoT environments with constrained resources. These findings highlight ASCON’s potential to address critical security needs in the rapidly evolving IoT landscape.